Az erdélyi magyar orvosképzés I. rész: Kolozsvár - Péterffy, Árpád (Gerundium, 2016)
Hungarian Medical Training in Transsylvania (1): Kolozsvár. The pertinent text first sketches a comprehensive survey of two periods of medical training (1872–1919 and 1940–1944) of the University of Kolozsvár, detailing the infrastructural progress of the institution, student enrollment figures, the everyday functioning of medicinal and scientific activities. The author passionately outlines the circumstances of the discontinuation of the training program on two separate occasions. As supplements to the text, the biographies of four rectors (university presidents who have played important roles in the development of the institution and of medical training) are included, together with lists of the departments and leading professors that played important roles in the two periods